Multifocal infantile haemangioma: a diagnostic challenge. (17th June 2016) - Torres, Erica; Rosa, João; Leaute-Labreze, Christine; Soares-de-Almeida, Luis
Abstract : We describe a case of a newborn who presented with multiple dark red macules that developed into red-to-purple papules associated with thrombocytopaenia. Abdominal ultrasound showed multiple hyperechoic papules and nodules. Endothelial cells from a skin biopsy stained positively for endothelial cell glucose transporter 1, which was consistent with a diagnosis of multifocal infantile haemangioma. At the age of 2 months, the child developed intestinal bleeding and anaemia. Upper and lower endoscopies showed no intestinal haemangiomas. Oral treatment with propranolol (3 mg/kg/day) resulted in complete involution of the skin and hepatic haemangiomas over the period of treatment, which lasted until the child was aged 15 months. This is a rare case of multifocal cutaneous haemangioma with hepatic and probable intestinal involvement, successfully treated with propranolol.